2022
DOI: 10.1039/d2tb01651f
|View full text |Cite
|
Sign up to set email alerts
|

Transition metallo-curcumin complexes: a new hope for endometriosis?

Abstract: The metallo-curcumin complexes, copper–curcumin and nickel–curcumin, are promising anti-endometriotic agents due to their high antioxidant activity, selective cytotoxicity and active transport mediated accumulation in endometriotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…As shown in Fig. 7(c), with various concentrations of HGPF (up to 200 μg mL −1 ), the hemolysis rates were all below the negative reaction limit of 5%, 55 demonstrating no obvious hemolysis was caused by HGPF. Therefore, HGPF was considered to be hemocompatible and was regarded as bio-safe for the potential therapeutic procedure.…”
Section: Resultsmentioning
confidence: 84%
“…As shown in Fig. 7(c), with various concentrations of HGPF (up to 200 μg mL −1 ), the hemolysis rates were all below the negative reaction limit of 5%, 55 demonstrating no obvious hemolysis was caused by HGPF. Therefore, HGPF was considered to be hemocompatible and was regarded as bio-safe for the potential therapeutic procedure.…”
Section: Resultsmentioning
confidence: 84%
“…The isolation protocol and subject selection for all the cell types used are described in detail in the Supporting Information Section DS3. The hESCs were also isolated by enzymatic digestion according to the protocol described elsewhere . The protocol is described in detail in section DS4, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The hESCs were also isolated by enzymatic digestion according to the protocol described elsewhere. 41 The protocol is described in detail in section DS4, Supporting Information. All experiments were carried out with cells ≤ passage 5.…”
Section: Fabrication Of Hybrid Stent By Combining Electrospinning And...mentioning
confidence: 99%
“…First, the combined use of Cu and curcumin was investigated. Although the addition of Cu effectively enhanced the effects of curcumin, in this case, this trace metal should be considered as an effective carrier rather than an active substance [ 109 ]. On the other hand, it was found that pharmacological reduction of copper levels may result in stopping the growth of endometriotic lesions.…”
Section: The Role Of Selected Dietary Components In the Course Of End...mentioning
confidence: 99%